GalaxyDock2‐HEME: Protein–ligand docking for heme proteins. Issue 14 (21st February 2023) - Lee, Changsoo; Yang, Jinsol; Kwon, Sohee; Seok, Chaok
Abstract: Prediction of protein–ligand binding poses is an essential component for understanding protein–ligand interactions and computer‐aided drug design. Various proteins involve prosthetic groups such as heme for their functions, and adequate consideration of the prosthetic groups is vital for protein–ligand docking. Here, we extend the GalaxyDock2 protein–ligand docking algorithm to handle ligand docking to heme proteins. Docking to heme proteins involves increased complexity because the interaction of heme iron and ligand has covalent nature. GalaxyDock2‐HEME, a new protein–ligand docking program for heme proteins, has been developed based on GalaxyDock2 by adding an orientation‐dependent scoring term to describe heme iron‐ligand coordination interaction. This new docking program performs better than other noncommercial docking programs such as EADock with MMBP, AutoDock Vina, PLANTS, LeDock, and GalaxyDock2 on a heme protein–ligand docking benchmark set in which ligands are known to bind iron. In addition, docking results on two other sets of heme protein–ligand complexes in which ligands do not bind iron show that GalaxyDock2‐HEME does not have a high bias toward iron binding compared to other docking programs. This implies that the new docking program can distinguish iron binders from noniron binders for heme proteins. Abstract : A protein–ligand docking method for heme proteins is developed based on GalaxyDock2 by incorporating a new coordination bond potential. Newly introduced weight parameters are optimized to maximize decoy discrimination on known heme protein–ligand complexes.